2020
DOI: 10.1002/brb3.1774
|View full text |Cite
|
Sign up to set email alerts
|

The inter‐relationship between diet, selflessness, and disordered eating in Australian women

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 49 publications
(92 reference statements)
0
11
0
Order By: Relevance
“…According to this approach, girls and women sacri ce their needs and starve themselves because of a poor sense of self [9]. Subsequent research with women has indeed found a signi cant association between sel essness and eating disorder symptoms [5,12,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to this approach, girls and women sacri ce their needs and starve themselves because of a poor sense of self [9]. Subsequent research with women has indeed found a signi cant association between sel essness and eating disorder symptoms [5,12,21].…”
Section: Discussionmentioning
confidence: 99%
“…Another factor relevant to the connection between disordered eating and both measures of self-de ciency that remains to be explored is gender. Whereas a connection between sel essness and disordered eating has been consistently observed in women [10,12], no published studies to date have examined sel essness and disordered eating in men. Nor has gender been adequately examined in relation to the connection between disordered eating and concern for appropriateness.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Selflessness is the tendency to relinquish one’s own interests and ignore one’s genuine needs in the service of others’ interests and well-being. Although this characteristic was conceptualized, defined and quantified in the context of patients with clinical eating disorders [ 26 ], an association between measures of disordered eating in the general population and scores on the Selflessness Scale (SS) [ 26 ] has consistently been found in research [ 26 , 27 , 29 31 ]. Selflessness has even been shown to predict the development of disordered eating over time [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The vegetarian diet is harder to characterised: while full vegetarians avoid meat and fish completely, there are different types of vegetarian diets, such as pescetarians (inclusion of fish) and ovo-vegetarians (inclusion of eggs) (Heiss et al, 2017a;Timko et al, 2012). Previous research has questioned if different dietary patterns might be associated with more vulnerability for disordered eating behaviours (Brytek-Matera, 2020;Collins & Quinton, 2020;Timko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%